Angular Deformities of the Lower Limb in Children - Espandar, Ramin (Tehran University of Medical Sciences, 2010)
Angular deformities of the lower limbs are common during childhood. In most cases this represents a variation in the normal growth pattern and is an entirely benign condition. Presence of symmetrical deformities and absence of symptoms, joint stiffness, systemic disorders or syndromes indicates a benign condition with excellent long-term outcome. In contrast, deformities which are asymmetrical and associated with pain, joint stiffness, systemic disorders or syndromes may indicate a serious underlying cause and require treatment. Little is known about the relationship between sport participation and body adaptations during growth. Intense soccer participation increases the degree of genu varum in males from the age of 16. Since, according to some investigations, genu varum predisposes individuals to more injuries, efforts to reduce the development of genu varum in soccer players are warranted. In this article major topics of angular deformities of the knees in pediatric population are practically reviewed.